The Improvement Of Lecturer’s Performance with Big Five Personality Traits Through Organizational Culture - Faizati, Ayu Niken; Muttaqin, Idzani; Rofam, Galuh Nashrulloh Kartika Mayangsari; Khuzaini (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The world of education continues to struggle with global competition to remain competitive and grow in the long term by emphasizing the importance of higher education institutions managing and maintaining the quality of lecturer performance. A theory concerning personality is the Big Five Personality model, which organizes numerous traits into five major categories that are commonly known as personality dimensions.  Research-based on Big Five Personality on the performance of lecturers is still very rarely conducted.  This can be due to the level of difficulty in terms of collecting and opening data on lecturer performance in private universities. This research design uses explanatory research, to test the impact of the big five personality on lecturer performance. The method used in this study was the PLS-SEM modelling method. The research was conducted involving 155 lecturers who were selected based on predetermined sample criteria. The results of the study show that the big five personalities have a significant effect on lecturer performance and organizational culture, while organizational culture has no effect on lecturer performance.